2021
DOI: 10.1101/2021.01.23.21250363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceived disrespect and abuse among women delivering at a tertiary care center in Nepal

Abstract: BackgroundOf the children born every year in Nepal, 57.4% are delivered in health facilities. Disrespect and abuse of women during maternity care are problems that can significantly impact women’s willingness to seek out life-saving maternity care. However, evidence suggests ongoing disrespectful maternity care worldwide. This study aims to identify perceived disrespect and abuse during labor and delivery among postnatal women delivering at Bheri Hospital, Nepal.MethodsA cross sectional study was conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This raises the challenge of how to measure RMC [14]. Client or provider interviews are most often reported in the literature [15][16][17][18]. However, there have been calls recommending a mixed-method approach, including independent observations to measure RMC [13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This raises the challenge of how to measure RMC [14]. Client or provider interviews are most often reported in the literature [15][16][17][18]. However, there have been calls recommending a mixed-method approach, including independent observations to measure RMC [13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A study in eastern Nepal revealed various forms of disrespect and abuse among women such as non-consented care, verbal and physical abuse, non-confidential care, and discriminatory care (Ghimire et al, 2021). Conversely, three studies from central and western parts of Nepal found high prevalence of RMC practices (Gurung et al, 2021;Munikar et al, 2021;Pathak & Ghimire, 2020). Two studies reported that although women received care that was friendly, abuse free, and non-discriminatory, they wanted more timely care (Munikar et al, 2021;Pathak & Ghimire, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, three studies from central and western parts of Nepal found high prevalence of RMC practices (Gurung et al, 2021;Munikar et al, 2021;Pathak & Ghimire, 2020). Two studies reported that although women received care that was friendly, abuse free, and non-discriminatory, they wanted more timely care (Munikar et al, 2021;Pathak & Ghimire, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…4,5,6 This has hampered the use of maternal health care programs, resulting in a decline in their health and well-being. 7 Women are vulnerable in any way during pregnancy, labor, or…”
Section: Introductionmentioning
confidence: 99%